2015
DOI: 10.1016/j.proci.2014.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Ignition delay time measurements behind reflected shock-waves for a representative coal-derived syngas with and without NH3 and H2S impurities

Abstract: The composition of a representative coal-derived syngas was determined by averaging 40 practical coal syngas compositions from the literature and corresponds to a departure from many recent studies which only focus on syngas blends containing just CO and H 2. Ignition delay times have been measured behind reflected shock waves for this averaged mixture with an equivalence ratio of 0.5 (0.4554% CO / 0.3297% H 2 / 0.1032% CO 2 / 0.0172% CH 4 / 0.2407% H 2 O / 0.8538% O 2 in 98% Ar (mol. %)) at around 1.7, 13, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, experimental investigations on the reactivity of reformate gases including small hydrocarbons are still quite limited while many studies have assessed the reactivity of pure CO/H 2 mixtures (Dryer and Chaos 2008;Frassoldati, Faravelli, Ranzi 2007;Nakamura et al 2016;Natarajan, Lieuwen, Seitzman 2007;Petersen et al 2007;Walton et al 2007). In order to compare target mixture conditions investigated in the present study and earlier works considering the reactivity of CO/H 2 mixtures with small hydrocarbons (Gersen, Darmeveil, Levinsky 2012;Liu et al 2018;Mansfield and Wooldridge 2015;Mathieu et al 2015;Mathieu, Kopp, Petersen 2013), a CO-H 2 -CH 4 ternary diagram is introduced (Figure 3). CH 4 is selected as a representative small hydrocarbon because it is the simplest hydrocarbon and the most likely to be included in reformate products besides CO and H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, experimental investigations on the reactivity of reformate gases including small hydrocarbons are still quite limited while many studies have assessed the reactivity of pure CO/H 2 mixtures (Dryer and Chaos 2008;Frassoldati, Faravelli, Ranzi 2007;Nakamura et al 2016;Natarajan, Lieuwen, Seitzman 2007;Petersen et al 2007;Walton et al 2007). In order to compare target mixture conditions investigated in the present study and earlier works considering the reactivity of CO/H 2 mixtures with small hydrocarbons (Gersen, Darmeveil, Levinsky 2012;Liu et al 2018;Mansfield and Wooldridge 2015;Mathieu et al 2015;Mathieu, Kopp, Petersen 2013), a CO-H 2 -CH 4 ternary diagram is introduced (Figure 3). CH 4 is selected as a representative small hydrocarbon because it is the simplest hydrocarbon and the most likely to be included in reformate products besides CO and H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 is selected as a representative small hydrocarbon because it is the simplest hydrocarbon and the most likely to be included in reformate products besides CO and H 2 . For each plot in Figure 3, the mole fractions of CO, H 2 and CH 4 are extracted from the literatures (Gersen, Darmeveil, Levinsky 2012;Liu et al 2018;Mansfield and Wooldridge 2015;Mathieu et al 2015;Mathieu, Kopp, Petersen 2013) and normalized. As might be readily apparent, most cases are located on several specific regions in the chart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were compared with previous work of Peschke and Spadaccini [21] indicating that their variations of ignition delay times over time agreed well, but there are deviations between experimental results and predictions. Mathieu et al [22,23] studied the ignition delay times of syngas derived from coal and biomass in a shock tube. The effects of other components (CH 4 , CO 2 , H 2 O, NH 3 , H 2 S) other than CO and H 2 on the ignition delays were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…of a large fraction of natural gas resources (so-called sour natural gas) [1]. Syngas blends produced from either coal or biomass can also contain H 2 S, up to 1.3% mol [2], and it has been shown that H 2 S, even in small proportion, can have a noticeable effect on important combustion properties such as ignition delay time ( ign ) [2,3] and flame speed [4] for hydrogen-based mixtures. For these reasons, H 2 S combustion chemistry has been the topic of several recent studies [1,3,[5][6][7][8][9].…”
mentioning
confidence: 99%